Analysis of the Energy and Economic Effects of Green Remodeling for Old Buildings: A Case Study of Public Daycare Centers in South Korea - Jeong-Heum Cho; Sangmu Bae; Yujin Nam (Energies, 2023)
In South Korea, green remodeling policies have been promoted to improve the energy performance of buildings, especially old buildings. Moreover, simultaneous improvement of both energy and structural performance has emerged as an important issue. Although several proposals have been made by different governments for the improvement of energy and structural performance, most were related to technological development or construction methods. Therefore, to simultaneously improve the energy and structural performance of old buildings, in this study, we performed an analysis to evaluate the feasibility of improvement based on an actual case of green remodeling of an old building. In addition, the expected social effects were analyzed by examining the effect of fiscal expenditure on employment, considering personnel and operating expenses. As a result, primary energy consumption was reduced by approximately ≥48% after green remodeling, and CO2 emissions during the building operation stage were reduced by approximately ≥46%. When green remodeling and structural retrofitting were performed concurrently, the construction cost was reduced by approximately ≥27% when overlapping items in the construction schedule were optimized. These findings are relevant to the setting of goals and the establishment of strategies during green remodeling and structural retrofitting of old buildings.